2017
DOI: 10.1136/bmjopen-2016-013881
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological guidelines for schizophrenia: a systematic review and comparison of recommendations for the first episode

Abstract: ObjectivesClinical practice guidelines (CPGs) support the translation of research evidence into clinical practice. Key health questions in CPGs ensure that recommendations will be applicable to the clinical context in which the guideline is used. The objectives of this study were to identify CPGs for the pharmacological treatment of first-episode schizophrenia; assess the quality of these guidelines using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument; and compare recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 61 publications
1
80
0
10
Order By: Relevance
“…Standard care for first-episode psychosis includes acute inpatient care and psychiatric outpatient clinic follow-up, with no assertive practices, psychoeducation, family intervention or cognitivebehavioural therapy for psychosis. There are about 10 teams in Portugal, mainly in the north and centre of the country, providing early detection, treatment and support to young people with psychosis according to international guidelines (International Early Psychosis Association Writing Group, 2005;Keating et al, 2017). Some of these teams also give care to individuals in the at-risk stage for psychotic disorders (at-risk of mental state) before the development of fullblown psychotic episode (Yung et al, 2005;Yung & Nelson, 2011 A significant proportion of patients presenting with FEP have an unclear clinical picture with different degrees of mood and psychotic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Standard care for first-episode psychosis includes acute inpatient care and psychiatric outpatient clinic follow-up, with no assertive practices, psychoeducation, family intervention or cognitivebehavioural therapy for psychosis. There are about 10 teams in Portugal, mainly in the north and centre of the country, providing early detection, treatment and support to young people with psychosis according to international guidelines (International Early Psychosis Association Writing Group, 2005;Keating et al, 2017). Some of these teams also give care to individuals in the at-risk stage for psychotic disorders (at-risk of mental state) before the development of fullblown psychotic episode (Yung et al, 2005;Yung & Nelson, 2011 A significant proportion of patients presenting with FEP have an unclear clinical picture with different degrees of mood and psychotic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine is still considered to date as the most effective antipsychotic (Sultan et al, 2017) and a meta-analysis confirmed the largest effect size among the newer generation antipsychotics . Since the pivotal study by Kane et al (Kane et al, 1988) found that about a third of stringently defined treatment-resistant patients responded to clozapine, it has been the gold standard medication in this specific population and is now recommended in international therapeutic guidelines (Abidi et al, 2017;Hasan et al, 2015Hasan et al, , 2013Howes et al, 2017b;Keating et al, 2017;Leucht et al, 2015;Lo et al, 2016;Remington et al, 2017;Samalin et al, 2013;Stahl et al, 2013). However, 40% still remain classified as resistant to clozapine, which has been called "ultra resistance to treatment in schizophrenia" (UTRS) (Siskind et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various guidelines have been published for the treatment of psychiatric disorders. [1][2][3][4][5][6][7][8] In many countries, psychiatrists usually treat patients based on treatment guidelines. However, evidence-based treatment guidelines for psychiatric disorders were not developed in Japan until 10 years ago; as a result, Japanese psychiatrists were likely to base clinical decisions on their own experiences.…”
Section: Discussionmentioning
confidence: 99%